2007
DOI: 10.5414/cnp67209
|View full text |Cite
|
Sign up to set email alerts
|

Association between biomarkers of inflammation and left ventricular hypertrophy in moderate chronic kidney disease

Abstract: Aims: Left ventricular hypertrophy (LVH) is a predictor for cardiovascular mortality, and it is considered to be a surrogate marker of preclinical cardiovascular disease. This study aimed at evaluating whether fetuin-A plasma levels are decreased in patients with moderate chronic kidney disease (CKD) and their linkage to plasma concentrations of hs-C-reactive protein (CRP), cardiotrophyn-1 (CT-1), tumor necrosis factor-a (TNF-a), propeptide of collagen Type I (PIP) and to LVH. Material and methods: We enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 32 publications
4
52
1
2
Order By: Relevance
“…18,19 In fetuin-A-deficient mice, the aorta was found to be devoid of calcification and fibrosis, whereas the peripheral vessels in the skin and kidney showed evidence of extensive calcification; furthermore, the small artery involvement preceded the impairment of renal function. 17,18,20 The data presented herein support the relationship between fetuin-A and IMT, suggesting that decreases in the fetuin-A level could have a role in the development of the vascular changes that are peculiar to hypertensive patients; this role appears to be independent of other confounding factors, such as renal function. Nevertheless the results of this study are not an unambiguous demonstration for the causative role of fetuin-A.…”
Section: Discussionsupporting
confidence: 71%
“…18,19 In fetuin-A-deficient mice, the aorta was found to be devoid of calcification and fibrosis, whereas the peripheral vessels in the skin and kidney showed evidence of extensive calcification; furthermore, the small artery involvement preceded the impairment of renal function. 17,18,20 The data presented herein support the relationship between fetuin-A and IMT, suggesting that decreases in the fetuin-A level could have a role in the development of the vascular changes that are peculiar to hypertensive patients; this role appears to be independent of other confounding factors, such as renal function. Nevertheless the results of this study are not an unambiguous demonstration for the causative role of fetuin-A.…”
Section: Discussionsupporting
confidence: 71%
“…However, we believe we covered typical times for routine practice. Fourth, the levels of CRP and ESR are influenced by the presence of systemic conditions [6,9,18,24]. In our study, we found no differences in the prevalence of the systemic conditions between the unilateral and staged bilateral groups.…”
Section: Discussioncontrasting
confidence: 39%
“…The data on the fortysecond and ninetieth postoperative days only were compared between the unilateral and the second knee bilateral groups. Because the levels of CRP and ESR are influenced by the presence of other systemic conditions (diabetes mellitus, cardiac diseases, chronic lung and kidney disease, and cancers) [6,9,18,24], proportions of patients with the systemic conditions were compared between the unilateral and the staged bilateral groups. There were no differences in the prevalence of systemic conditions between the unilateral and staged bilateral groups (20.3% versus 27.9%; p [ 0.05, chi square test).…”
Section: Methodsmentioning
confidence: 99%
“…In particular, it has been claimed that these factors have a role of the development of LVH in dialysis patients. [9,15] LVH is an important indicator of increased cardiovascular risk in ESRD patients [10] ; therefore, it is very important to define the factors leading to development of LVH. Visfatin, which is suggested to be related to inflammation and endothelial dysfunction, may be responsible of the Comparison of IL-6 serum levels between CAPD and hemodialysis patients and healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[3,6] Increased levels of IL-6 and TNF-α have been demonstrated to be related with left ventricular hypertrophy (LVH) in dialysis patients. [8][9][10] This suggests a relationship between visfatin, which is thought to be a proinflammatory cytokine, and LVH, though such a relationship has not yet been explored in the literature.…”
Section: Introductionmentioning
confidence: 99%